ChemInform Abstract: An Efficient Iron Catalyzed Regioselective Acylative Cleavage of Ethers: Scope and Mechanism. Issue 16 (March 2016) - Bodduri, V.D. Vijaykumar; Choi, Kyung‐Min; Vaidya, Raghavender Rao; Patil, Kalpesh; Chirumarry, Sridhar; Jang, Kiwan; Yoon, Yong‐Jin; Falck, John R.; Shin, Dong‐Soo
Abstract: Regioselective cleavage of cyclic and acyclic ethers in the presence of acid chlorides yields chloro‐esters and nonchlorinated esters, respectively.